2021
DOI: 10.1016/j.jcmgh.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Mucosal Cholinergic Innervation Is Associated With Increased Risk of Enterocolitis in Hirschsprung’s Disease

Abstract: Lacking colonic mucosal innervation correlated with increased inflammatory immune cell status, microbial dysbiosis, and higher incidence of postoperative enterocolitis in HSCR patients. Mucosal nerve fibers might serve as a prognostic marker for enterocolitis development and offer new therapeutic intervention strategies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 71 publications
0
35
3
Order By: Relevance
“…Eltze and Figala (1988) M 1 R Ant 1-16 mg/day PO, 2.5-5 mg IM/IV Parkinson's disease, extrapyramidal symptoms Dicyclomine (Bentyl) Giachetti et al (1986) M 1 R Ant 20-160 mg/day PO Irritable bowel syndrome Pirenzipine (Gastrozepin) Bolden et al (1992) M 1 R Ant 100-150 mg/day PO Peptic ulcer disease Trihexyphenidyl (Artane) Giachetti et al (1986) M Hargreaves et al, (1992) M 1 R, M 3 R Agonist Oxotremorine Veena et al, (2011) M As a result of their central role in maintaining homeostasis in the GI tract, dysregulated MR signaling can be an important modifier of intestinal disease. In Hirschsprung disease, lack of mucosal cholinergic innervation in aganglionic colon segments increases the risk of postoperative enterocolitis (Keck et al, 2021). In diarrhea-predominant irritable bowel syndrome (IBS-D) without a concomitant psychiatric disorder, pyridostigmine (an acetylcholinesterase inhibitor) induces a stronger IL-6 response that is highly correlated with symptoms (Dinan et al, 2008).…”
Section: Muscarinic Receptor Distribution and Post-receptor Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Eltze and Figala (1988) M 1 R Ant 1-16 mg/day PO, 2.5-5 mg IM/IV Parkinson's disease, extrapyramidal symptoms Dicyclomine (Bentyl) Giachetti et al (1986) M 1 R Ant 20-160 mg/day PO Irritable bowel syndrome Pirenzipine (Gastrozepin) Bolden et al (1992) M 1 R Ant 100-150 mg/day PO Peptic ulcer disease Trihexyphenidyl (Artane) Giachetti et al (1986) M Hargreaves et al, (1992) M 1 R, M 3 R Agonist Oxotremorine Veena et al, (2011) M As a result of their central role in maintaining homeostasis in the GI tract, dysregulated MR signaling can be an important modifier of intestinal disease. In Hirschsprung disease, lack of mucosal cholinergic innervation in aganglionic colon segments increases the risk of postoperative enterocolitis (Keck et al, 2021). In diarrhea-predominant irritable bowel syndrome (IBS-D) without a concomitant psychiatric disorder, pyridostigmine (an acetylcholinesterase inhibitor) induces a stronger IL-6 response that is highly correlated with symptoms (Dinan et al, 2008).…”
Section: Muscarinic Receptor Distribution and Post-receptor Signalingmentioning
confidence: 99%
“…As a result of their central role in maintaining homeostasis in the GI tract, dysregulated MR signaling can be an important modifier of intestinal disease. In Hirschsprung disease, lack of mucosal cholinergic innervation in aganglionic colon segments increases the risk of postoperative enterocolitis ( Keck et al, 2021 ). In diarrhea-predominant irritable bowel syndrome (IBS-D) without a concomitant psychiatric disorder, pyridostigmine (an acetylcholinesterase inhibitor) induces a stronger IL-6 response that is highly correlated with symptoms ( Dinan et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…To learn more about enterocolitis, Keck et al 2 studied colons removed from 44 children during Hirschsprung disease pull-through surgery. As Meier-Ruge et al 3 observed in 1972, colon that lacks enteric nervous system often has abundant acetylcholinesterase staining, so acetylcholinesterase analysis is routinely used at many medical centers as part of Hirschsprung disease diagnosis.…”
mentioning
confidence: 99%
“…In contrast, Treg cells are generated from naive T cells in the presence of TGF-β and IL2. Keck et al 2 found that macrophages isolated from fiber-low and fiber-high colon both had a gut imprinted M2 phenotype (CX3CR1, AREG, AhR, CSR1R, CD200R, CD209, TGF-β2, IL10), but more macrophages from the fiber-low colon were IL23+, and fiber-low macrophages had higher mRNA levels of the Th17-inducing cytokines IL23a (an IL23 subunit) and IL6 and of the IL17 chemokine CCL-20. Interestingly, CD64+ macrophages closely associated with nerve fibers in submucosa of fiber-high colons and were more likely to have a bipolar shape typical of anti-inflammatory (M2) macrophages instead of the rounded or stellate shape typical of proinflammatory (M1) macrophages.…”
mentioning
confidence: 99%
See 1 more Smart Citation